2005
DOI: 10.1002/cncr.21430
|View full text |Cite
|
Sign up to set email alerts
|

Primary pediatric brain tumors

Abstract: MR‐guided transrectal prostate biopsy is currently a time‐consuming procedure because the imaging slice is often manually realigned with the biopsy needle during lesion targeting. In this work a pulse sequence is presented that automatically follows a passive marker attached to a dedicated MR biopsy device holder, thus providing an alternative to existing active tracking methods. In two orthogonal tracking FLASH images of the marker the position of the needle axis is automatically identified using a phase‐only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(42 citation statements)
references
References 39 publications
4
37
1
Order By: Relevance
“…Most of the investigations have stated that craniopharyngiomas rank next to medulloblastomas in their incidence rate [3,4,5, 10,14,15,16,17,18,19,20,21,22,23]. However, in our study, craniopharyngiomas made up approximately 18.4% of brain tumors only after astrocytic tumors.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Most of the investigations have stated that craniopharyngiomas rank next to medulloblastomas in their incidence rate [3,4,5, 10,14,15,16,17,18,19,20,21,22,23]. However, in our study, craniopharyngiomas made up approximately 18.4% of brain tumors only after astrocytic tumors.…”
Section: Discussioncontrasting
confidence: 51%
“…Our results indicate that more than half of this tumor type occurred in the 6- to 11-year age group where the highest incidence of high-grade brain tumors of neuroepithelial tissue was observed, but was uncommon in the early and late childhood period. The largest group of primary intracranial GCTs was reported in Japan, Taiwan and far eastern countries with an incidence of 10–14% of the brain tumors [14, 20, 24, 27]. In our analysis, GCTs were most common in the 12- to 14-year age group; in the 9- to 17-year age groups, they comprised 78.6% of all GCT cases.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…With 100–150 new cases each year in Taiwan, more than 986 cases were treated in TVGH from 1975 to May 2004 19. All patients were treated and followed by the same team, comprised of pediatric neurosurgeons, pathologists, neuroradiologists, pediatric neuro‐oncologists, and radiation oncologists.…”
Section: Methodsmentioning
confidence: 99%
“…This slight prevalence of males over females reflects the gender distribution of the population at risk, the same was found in a Kuwaiti study [13], where male slight preponderance was reported. In another study [14], where the male-tofemale ratio was 1:3, indicated that the pediatric brain tumors were more prevalent in males than in females and other studies found that too [1,15,18].…”
Section: Discussionmentioning
confidence: 93%